2017
DOI: 10.18203/issn.2454-5929.ijohns20174330
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of endoscopic versus conventional septoplasty: an analysis of 50 cases

Abstract: <p class="abstract"><strong>Background:</strong> Nasal obstruction is the most common complaint in ENT practice. Surgical correction of deviated nasal septum has been performed by a variety of techniques of which sub mucous resection and Septoplasty procedures of surgical correction of nasal septum play a prime role in management of patients of nasal obstruction. Nasal endoscope is very useful tool to visualize posterior part of septum and do the surgery more precisely and with less complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…10 Similar study conducted by Chandra et al, they observed that 92% (n=23) of group A and 88% (n=22) of group B were relieved from nasal discharge, while nasal obstruction was improved in 96% (n=24) patients of group A and 80% (n=20) of group B. 11…”
Section: Discussionmentioning
confidence: 64%
“…10 Similar study conducted by Chandra et al, they observed that 92% (n=23) of group A and 88% (n=22) of group B were relieved from nasal discharge, while nasal obstruction was improved in 96% (n=24) patients of group A and 80% (n=20) of group B. 11…”
Section: Discussionmentioning
confidence: 64%
“…We used a standardised form 7–9 . The analysed outcomes were the post‐treatment NOSE scale and the percentage of patients who fully recovered from NSD or complications of septoplasty 6,10–46 . These results were compared between the endoscopic septoplasty and control (conventional septoplasty) groups.…”
Section: Methodsmentioning
confidence: 99%